Curettage and Cementation in Giant Cell Tumour of the Distal Tibia Using Polypropylene Mesh for Containment: A Case Report - K.L, Pan; W.H, Chan (Malaysian Orthopaedic Journal, 2010)
Giant cell tumours of bone are best treated by extended curettage and filling in of the defect with cement or bone graft. In more advanced stages, when there is extensive loss of cortical bone cover, containment of the filling material is not possible and resection and reconstruction is required. We report a case of a recurrent giant cell tumour of the distal tibia in a 21-year-old female with extensive cortical bone loss in which polypropylene surgical mesh was used to contain the bone cement, thus avoiding a resection.